USP21-EGFR signaling axis is functionally implicated in metastatic colorectal cancer - Ji Hye Shin; Mi-Jeong Kim; Ji Young Kim; Bongkum Choi; Yeeun Kang; Seo Hyun Kim; Ha-Jeong Lee; Dohee Kwon; Yong Beom Cho; Kyeong Kyu Kim; Eunyoung Chun; Ki-Young Lee (Cell Death Discovery)
Abstract The emerging role of ubiquitin-specific peptidase 21 (USP21) in stabilizing Fra-1 (FOSL1) highlights its involvement in promoting colorectal cancer (CRC) metastasis. Additionally, a reciprocal link between EGFR signaling and Fra-1 activation has been identified, mediated through matrix metalloproteinases (MMPs). However, the functional implications of the USP21-EGFR signaling axis in metastatic CRC (mCRC) are not fully understood. To investigate the clinical correlation between USP21 and EGFR expression, RNA-Seq data from tumor tissues (n = 27) and matched normal tissues (n = 27) of 27 mCRC patients were analyzed. Functional studies were performed, including the use of CRISPR/Cas9 to generate USP21-knockout (USP21-KO) CRC cells, in vitro assays for cancer progression and tumor formation, in vivo xenograft assays in NSG mice. Additionally, the therapeutic effect of the USP21 inhibitor, BAY-805, was evaluated. We found that elevated levels of USP21 and EGFR expression in mCRC patients were associated with poorer survival outcomes. Mechanistically, USP21 was found to enhance EGFR stability by deubiquitinating EGFR, leading to reduced EGFR degradation. USP21-KO colon cancer cells exhibited significantly reduced proliferation, migration, colony formation, and 3D tumor spheroid formation in response to EGF. Furthermore, the tumorigenic activity in vivo was markedly diminished in NSG mice xenografted with USP21-KO colon cancer cells. Importantly, BAY-805 demonstrated a notable inhibitory effect on the formation of 3D tumor spheroids in colorectal cancer cells stimulated with EGF. These findings suggest that USP21 could be a valuable therapeutic target and predictive biomarker for managing mCRC driven by EGF.